Real-world experience with anti–programmed cell death protein 1 immunotherapy in patients with esophageal cancer: A retrospective single-center study - Wang, Xinpeng; Cai, Lvjuan; Wu, Mengjing; Li, Guo; Zhu, Yunyun; Lin, Xinyue; Yan, Xue; Mo, Peng; Luo, Huachun; Fu, Zhichao (Frontiers in Oncology, 2022)
The “real-world” data of programmed cell death protein 1 (PD-1) inhibitors in esophageal cancer (EPC) are still an unmet medical need, including the clinical efficacy and safety. Seventy-seven EPC data were studied retrospectively; the progression-free survival (PFS), risk factors (clinical stages larger than stage II, metastatic sites larger than 2, treatment lines larger than the first line, previous surgical treatment, combined positive score [CPS] expression, etc.), and the safety were analyzed. The median PFS for all patients was 7.2 months, clinical stage > stage II; the number of treatment lines > first line was significantly correlated with prognosis (all P < 0.05). Subgroup analysis showed that the median PFS of patients with clinical stage ≤ II was better; the results were the same for the patients with ≤2 metastatic sites, first-line PD-1 inhibitors, and not previously received radical surgery (all P < 0.05). Meanwhile, the incidence of adverse events (AEs) of varying degrees was 25.97% (20/77) in 20 patients and 6.49% (5/77) of grade 3/4 AEs. The highest AE was myelosuppression (15.58%), followed by liver function injury (7.79%). In addition, ≥2 lines of treatment and >2 metastatic sites predicted poor outcomes for patients with EPC who had failed first-line therapy or progressed with the combined immunotherapy and chemotherapy treatment strategy (all P < 0.05).